The Criminology and Peacemaking Possibilities of The Purge Film and TV Series - Finley, Laura (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
As has been widely noted, film both reflects and shapes social reality. Films represent current social, political, economic and cultural trends and shape societal perceptions and ideas (Welsh, Fleming & Dowler, 2011). As hooks (1996) wrote, “Whether we like it or not, cinema assumes a pedagogical role in the lives of many people” (p. 2).Yet media constructions of crime are often inaccurate or misleading, overrepresenting predatory violent crime perpetrated by the poor and underrepresenting crime by elites (Coyne & Archer, 2004; Surrette, 2011). Also overrepresented are retributive, punitive systems and underrepresented are restorative practices (Raney, 2005).